Prediction of crack depth and fatigue life of an acrylonitrile butadiene styrene cantilever beam using dynamic response - Zai, Behzad Ahmed; Khan, Muhammad A.; Khan, Sohaib Z.; Asif, Muhammad; Khan, Kamran Ahmed; Saquib, Ahmad N.; Mansoor, Asif; Shahzad, Majid; Mujtaba, Ahmed (ASTM International, 2019)
n this article, a methodology is proposed that can be used to predict the crack growth and fatigue life of a cantilever beam made of Acrylonitrile Butadiene Styrene (ABS) manufactured with fused deposition modeling. Three beam configurations based on length (L = 110, 130, and 150 mm) are considered. Empirical relationships are formulated between the natural frequency and the crack growth. The analytical and experimental results are found to be in good agreement for all configurations. Using the experimental data, a global relation is formulated for the crack depth prediction. This global relation is useful for an in situ crack depth prediction with an error of less than 10 %. Later, a residual fatigue life of these specimens is compared with a metallic structure (Aluminum 1050) of similar configuration available in the literature. It is found that the ABS material has more residual fatigue life compared with the metallic structure at the same frequency drop. Based on the remaining fatigue life, ABS material can be a potential material to manufacture machine components under cyclic loads.
Keywords: fused deposition modeling; dynamic response; crack growth; Natural frequency; Residual fatigue life